Kontribusi Sektor UMKM terhadap Penerimaan Pajak Negara di Indonesia - Siti Dzulhijjah; Nur Ramadina Yasin; Putri Maharani Kusumawati; Fasya Hilwa Az-zahra; Muhammad Ilham Pero (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economic growth by creating employment opportunities and contributing significantly to the national GDP. However, their contribution to the country’s tax revenue remains relatively low compared to their overall economic impact. This study aims to examine the contribution of the MSME sector to Indonesia’s tax revenue and to identify the factors influencing this contribution level. The research employs a descriptive quantitative approach using secondary data from Statistics Indonesia (BPS), the Directorate General of Taxes (DGT), and the Ministry of Finance covering the period 2018–2023. The findings indicate that the tax contribution from MSMEs has gradually increased over the years, although it still accounts for less than one percent of total national tax revenue. This positive trend is supported by the implementation of lower tax rates, the digitalization of tax systems, and the growing tax awareness among business owners. The study suggests that further administrative simplification and stronger government support are essential to enhance the role of MSMEs in strengthening Indonesia’s fiscal capacity